Circulating tumour necrosis factor-α bioactivity in rheumatoid arthritis patients treated with infliximab: link to clinical response - Marotte, Hubert (BioMed Central, 2005)
Our objective was to clarify the heterogeneity in response to infliximab treatment in rheumatoid arthritis (RA); to this end, a bioassay was designed to explore the contribution of circulating tumour necrosis factor (TNF)-α bioactivity and its possible link to response. The bioassay is based on the induction of IL-6 and osteoprotegerin (OPG) production by synoviocytes in response to TNF-α. RA synoviocytes were cultured with TNF-α (5 ng/ml) and 42 RA plasma samples collected just before starting therapy. Levels of IL-6 and OPG were measured in supernatants. In 20 of the patients, plasma samples collected before and 4 hours after the first and the ninth infusions were tested in the same way. Plasma concentrations of TNF-α and p55 and p75 soluble receptors were measured using ELISA. TNF-α induced IL-6 and OPG production by synoviocytes, which was further increased with patient plasma dilutions and inhibited by infliximab. With plasma samples obtained before the first infusion, the IL-6-induced production was greater in patients with a good clinical response than in the poor responders (44.4 ± 23.3 ng/ml versus 27.4 ± 20.9 ng/ml; P = 0.05). This high circulating TNF-α bioactivity was strongly inhibited with the first infliximab infusion. The difference between IL-6 levels induced with plasma samples obtained before and 4 hours after the first infusion was greater in patients with a good clinical response (40.0 ± 23.7 ng/ml versus 3.4 ± 10.0 ng/ml; P = 0.001). Similar findings were obtained for OPG production (7.0 ± 6.2 ng/ml versus 0.0 ± 3.0 ng/ml; P < 0.05). Levels of circulating TNF-α bioactivity were predictive of clinical response to TNF-α inhibition, confirming a key role for TNF-α in these RA patients.